Student Motivation and Self-Concept: Is There a Connection? - Frade, Ana (2017)
The concept of motivation has been placed at the heart of discussions related to academic achievement and school withdrawal. Student and trainee self-concept is presented – throughout the reviewed literature – as an effective response for schools as well as an aspect to consider when promoting motivation and performance in students. Several studies argue that self-concept is the foundation of motivated behaviour. The present study reviews the literature concerning the connections between student motivation and self-concept, highlighting their importance in academic performance. Trainee motivation is also characterized here with respect to self-concept through information collected from a sample comprising 149 trainees from the Training Course for Petty Officers 1st Class by applying the Assessment Scale for Trainee Self-concept in the Portuguese Navy (ASTSC-PN) (Frade & Veiga, 2016) and the Learning Motivation Scale (LMS) (Frade, 2015; Frade & Veiga, 2014). The data were analysed using SPSS software. The result analysis allowed the finding of connections between trainee motivation and personal variables. It is intended that the gathered information contributes to support and validate the theoretical constructs presented here.